Aplikasi Pengolahan Data Surat Izin Usaha Angkutan Barang pada Kantor Dinas Perhubungan Kabupaten Lima puluh Kota - Irohito Nozomi; Muhammad Luthfi Hamzah (INTECOMS: Journal of Information Technology and Computer Science, 2018)
The ability and speed of computers in processing data repeatedly and with a very large number is no doubt to produce the reports needed in the process of strategic decision-making. So at this time has been many companies and government agencies want to use computer technology to help solve their data processing problems. In the Office of Transportation (DISHUB) of Kabupaten Lima Puluh Kota, the data processing business licenses have been conducted frequently, but have not obtained accurate results. This is due to the use of information technology is still very less and implemented manually. The accuracy of the data is necessary to avoid irregularities and errors in reports. Application System will be proposed later using PHP programming language and MYSQL. All data entry will be processed in a Database. Diverse data will be more easily and quickly processed in a well-structured system. Keywords :Data Processing, PHP, MYSQL